LOKASI OPTIMAL PENGEMBANGAN TPI UNTUK MENDUKUNG PERKEMBANGAN KAWASAN PESISIR KECAMATAN KRAGAN KABUPATEN REMBANG - Khristiana Dwi Astuti; Ricye Viyetri (Department of Urban and Regional Planning, Diponegoro University, 2014)
Geographically, District Kragan is located in northern coast of Java in Rembang Regency. Based on that, one of the potential sector in the district is marine fisheries. That sector is an alternative livelihood and increase the economy of Rembang Regency. To support the marine fisheries sector, it needed adequate infrastructure, such as fish comercial trader (a.k.a.TPI). There are 3 TPI in District Kragan: TPI Pandangan, TPI Karanglincak, and TPI Karanganyar, but not operating optimally. So, there’s less result of productivity, processing and marketing of fish in District Kragan. That problem effect on people's income and revenue of District Kragan.The method that used is quantitative methods, and approach to determine the minimum time and cost, marketing area, and maximum profit. In addition to analyzing the availability of infrastructure and facilities that support the development of coastal areas Kragan is using scoring analysis. Base on that analysis, the optimal location of the development of TPI in the District Kragan is on TPI Padangan because it has a large area, and thus allowing to support the development of TPI and accommodate the availability of infrastructure and facilities.